A monoanionic NNNN-type macrocyclic ligand for electropositive metal centers. Issue 22 (15th February 2018) - Mukherjee, Debabrata; Okuda, Jun
Abstract : The mono(amido) triamine macrocyclic ligand Me3 TACD [(Me3 TACD)H = 1, 4, 7-trimethyl-1, 4, 7, 10-tetraazacyclododecane] is a versatile supporting ligand for a variety of electropositive metals. Abstract : The coordination of a mono(amido) triamine macrocyclic ligand Me3 TACD derived from cyclen (1, 4, 7, 10-tetraazacyclododecane or [12]aneN4 ) toward electropositive metal centers is surveyed. This NNNN-type monoanionic macrocyclic ligand is capable of stabilizing a variety of metal coordination environments that are commonly not amenable to stable coordination spheres. Metal complexes supported by Me3 TACD include hydrides, hydrocarbyls, silyls, and amides. Protection of one hemisphere of a large metal center allows, as in the case of metallocene scaffolds for early transition metals, deaggregation and control of reactivity.